2021
DOI: 10.1186/s12872-021-02357-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of multimedia education in combination with teach-back method on quality of life and cardiac anxiety in patients with heart failure: a randomized clinical trial

Abstract: Background Education can contribute to promotion of the quality of life and reduction of heart anxiety in patients with heart failure, so it is important to find a suitable educational method for these patients. Therefore, the present study was an attempt to determine the effect of multimedia education using teach-back method on the life quality and cardiac anxiety in patients with heart failure. Methods The present study was a randomized clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Current guidelines recommend the inclusion of family care partners in HF care, particularly in the context of HF education and hospital-to-home transitions 45 . In line with this recommendation, all but 3 of the original research papers in this review mention family care partners in the context of their teach-back interventions 32,38,46 . One intervention was designed specifically for care partners (ie, no patients were enrolled), and demonstrated promising effects, such as high levels of satisfaction and significant reductions in care-related burden 47 .…”
Section: Teach-back In the Family Care Contextmentioning
confidence: 94%
See 1 more Smart Citation
“…Current guidelines recommend the inclusion of family care partners in HF care, particularly in the context of HF education and hospital-to-home transitions 45 . In line with this recommendation, all but 3 of the original research papers in this review mention family care partners in the context of their teach-back interventions 32,38,46 . One intervention was designed specifically for care partners (ie, no patients were enrolled), and demonstrated promising effects, such as high levels of satisfaction and significant reductions in care-related burden 47 .…”
Section: Teach-back In the Family Care Contextmentioning
confidence: 94%
“…45 In line with this recommendation, all but 3 of the original research papers in this review mention family care partners in the context of their teach-back interventions. 32,38,46 One intervention was designed specifically for care partners (ie, no patients were enrolled), and demonstrated promising effects, such as high levels of satisfaction and significant reductions in care-related burden. 47 Some study interventions that primarily focused on patient education but included care partners also report beneficial effects, such as increased engagement or satisfaction with care.…”
Section: Knowledge and Self-care Of Heart Failurementioning
confidence: 99%
“… 1 Dyspnea and tiredness, which cause exercise intolerance, and fluid retention, which cause pulmonary congestion and peripheral edema, are the typical signs of heart failure. 2 Every year, as many as 3.6 million patients in Europe receive a heart failure diagnosis. A total of 5.7 million people above 20 years of age in the US have heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…The American Heart Association has reported that cardiovascular disease is responsible for 22% of mortalities per year. In Iran, heart failure is the most common cause of hospitalization at hospital, as in every 100,000 Iranian people, around 3700 suffer from heart failure ( 3 ). The one-year mortality rate of HF in Iran has been 32% ( 4 ).…”
Section: Introductionmentioning
confidence: 99%